2021
DOI: 10.1016/j.jinf.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Short durations of corticosteroids for hospitalised COVID-19 patients are associated with a high readmission rate

Abstract: Objective Our objective was to describe the characteristics of patients admitted, discharged and readmitted, due to COVID-19, to a central London acute-care hospital during the second peak, in particular in relation to corticosteroids use. Methods We reviewed patients admitted from the community to University College Hospital (UCH) with COVID-19 as their primary diagnosis between 1st-31st December 2020. Re-attendance and readmission data were collected for patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 5 publications
(2 reference statements)
1
24
1
Order By: Relevance
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…16 In studies reporting on rates of hospital readmissions after COVID-19 hospitalization, treatments included including hydroxychloroquine, lopinavir/ritonavir, corticosteroids, anticoagulants and remdesivir. 4,[17][18][19][20] A study with a small number of patients treated with remdesivir reported 0/22 patients readmitted within 30 days. 4 By comparison, other treatments such as hydroxychloroquine and corticosteroids, were not associated with a reduction in hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…During COVID-19, many countries have reported remarkably high incidences of self-medication and home remedies among infected as well as uninfected people ( Fig 1 a), which may have had high probabilities of incorrect dosages. Extensive use of steroids during COVID-19 lockdown period has been observed in India, which seems to be the highest ever at the global level 29 . There has been a trend towards increased use of different antibiotics, steroids, vitamins, and Zn, etc.…”
Section: Self-medication Drugs Overuse and Microbial Dysbiosis: Effects On Immune Systemmentioning
confidence: 99%